THE EFFECT OF GREEN ORGANIZATIONAL CULTURE, GREEN TRANSFORMATIONAL LEADERSHIP AND JOB SATISFACTION ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR WITH ORGANIZATIONAL COMMITMENTAS A MEDIATION VARIABLE AT LANGSA CITY GENERAL HOSPITAL - Hasrianti; Ibrahim Qamarius; Yanita; Faisal Matriadi; Yulius Dharma; Darmawati Mucthar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study examines the influence of Green Organizational Culture, Green Transformational Leadership, Job Satisfaction on Organizational Commitment and Organizational Citizenship Behavior, and tests the mediation effect of the Organizational Commitment variable. The sample in this study was 143 employees at Langsa City General Hospital. The analysis tool used was path analysis with the SEM (structural equation modeling) method using Amos. The results showed that each variable Green Organizational Culture, Green Transformational Leadership and Job Satisfaction had a positive and significant effect on Organizational Commitment and Organizational Citizenship Behavior and the Organizational Commitment variable mediated Green Organizational Culture with the Organizational Citizenship Behavior variable in full mediation and the Organizational Commitment variable mediated Green Transformational Leadership with the Organizational Citizenship Behavior variable in full mediation, and also the Organizational Commitment variable mediated Green Transformational Leadership with the Organizational Citizenship Behavior variable in full mediation